Pancreatic stump closure using only stapler is associated with high postoperative fistula rate after minimal invasive surgery - Yüksel, Adem; Bostancı, Erdal Birol; Çolakoğlu, Muhammet Kadri; Ulaş, Murat; Özer, İlter and Karaman, Kerem and Akoğlu, Musa (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Postoperative pancreatic fistula (POPF) is the most common cause of morbidity and mortality after distal pancreatectomy (DP). The aim of the present study is to determine the risk factors that can lead to POPF. Materials and Methods: The study was conducted between January 2008 and December 2012. A total of 96 patients who underwent DP were retrospectively analyzed. Results: Overall, 24 patients (25%) underwent laparoscopic distal pancreatectomy (LDP) and 72 patients (75%) open surgery. The overall morbidity rate was 51% (49/96). POPF (32/96, 33.3%) was the most common postoperative complication. Grade B fistula (18/32, 56.2%) was the most common fistula type according to the International Study Group on Pancreatic Fistula definition. POPF rate was significantly higher in the minimally invasive surgery group (50%, p=0.046). POPF rate was 58.6% (17/29) in patients whose pancreatic stump closure was performed with only stapler, whereas POPF rate was 3.6% (1/28) in the group where the stump was closed with stapler plus oversewing sutures. Both minimally invasive surgery (OR: 0.286, 95% CI: 0.106-0.776, p=0.014) and intraoperative blood transfusion (OR: 4.210, 95% CI: 1.155-15.354, p=0.029) were detected as independent risk factors for POPF in multi-variety analysis. Conclusion: LDP is associated with a higher risk of POPF when stump closure is performed with only staplers. Intraoperative blood transfusion is another risk factor for POPF. On the other hand, oversewing sutures to the stapler line reduces the risk of POPF. Cite this article as: Yüksel A, Bostancı EB, Çolakoğlu MK, et al. Pancreatic stump closure using only stapler is associated with high postoperative fistula rate after minimal invasive surgery. Turk J Gastroenterol 2018; 29: 191-7.